Kontribusi pemikiran schleiermacher dalam hermeneutika sebagai sebuah revolusi penafsiran - Sutrisno, Febby Intansari Nuraini (Maliki Interdisciplinary Journal, 2025)
This study examines the contribution of Friedrich Schleiermacher's thought to the development of hermeneutics, as well as his views on the revolution of interpretive methods. Schleiermacher is considered one of the main pioneers in modern hermeneutics, who introduced a systematic and comprehensive approach to understanding texts. This study explores Schleiermacher's main ideas, which emphasize the importance of understanding texts in their overall context and the reciprocal relationship between the parts and the whole of the text. This study also discusses the impact and relevance of Schleiermacher's thought to the development of contemporary hermeneutics. Using qualitative analysis methods and literature reviews, this study shows that Schleiermacher's contribution not only broadens the horizon of hermeneutics as an academic discipline but also provides a foundation for more holistic and interdisciplinary approaches to interpreting texts.